2021
DOI: 10.1177/08862605211023485
|View full text |Cite
|
Sign up to set email alerts
|

Blaming Children: How Rape Myths Manifest in Defense Attorneys’ Questions to Children Testifying About Child Sexual Abuse

Abstract: Since rape myths were codified in 1980 ( Burt, 1980 ), scholars have shown that individuals who endorse rape myths perceive victims as less credible and more responsible for rape and perpetrators as less responsible. Studies also show that rape myths hinder successful adjudication of rape cases by influencing juries’ assessments of perpetrator guilt ( Dinos et al., 2015 ). While most of this research focuses on sexual assaults involving adult victims, some scholars have found that victims as young as 12 are bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This age-sensitive questioning may be somewhat strategic as disclosure patterns vary with child age (McElvaney, 2008). In further support, St George et al (2022a) found that defense attorneys used different strategies to employ rape myths across different age groups in ways that were plausible and realistic. Again, these tactics may be purposeful as children’s abuse experiences and ability to communicate these experiences are not static across age groups.…”
Section: Child Sexual Abuse Mythsmentioning
confidence: 90%
See 3 more Smart Citations
“…This age-sensitive questioning may be somewhat strategic as disclosure patterns vary with child age (McElvaney, 2008). In further support, St George et al (2022a) found that defense attorneys used different strategies to employ rape myths across different age groups in ways that were plausible and realistic. Again, these tactics may be purposeful as children’s abuse experiences and ability to communicate these experiences are not static across age groups.…”
Section: Child Sexual Abuse Mythsmentioning
confidence: 90%
“…The present work serves to complement and expand upon St George et al 2022a paper to explore how both well-established and novel CSA myths are used by defense attorneys during the cross examination of children alleging CSA. In the current study we use the same dataset as St George et al (2022a) to examine how CSA myths related to disclosure, witnesses and privacy, assumptions of harm, and the child’s relationship with their perpetrator appear across defense attorney questioning of children testifying about allegations of CSA. Furthermore, we examine how these myths manifest differently across child age.…”
Section: Child Sexual Abuse Myths and Misunderstandings In Courtmentioning
confidence: 95%
See 2 more Smart Citations
“…This means creating a safe environment for unaccompanied children, offering them care, and living conditions that meet their needs and vulnerabilities, and offer effective protection. Third, redouble efforts to fight criminal networks smugglers and traffickers (George et al, 2021;Hallet, 2016). And four measures can significantly help reduce the number of missing unaccompanied children: Provide quality reception and accommodation in foster care and small units in line with existing child protection standards such as the UN Alternative Care Guidelines; Ensure prompt appointment of trained and qualified guardians for all unaccompanied children; Build-up trust; Consider measures to ensure prompt family reunification procedures and early identification and implementation of durable solutions 18 .…”
Section: Special Situation About Refugeesmentioning
confidence: 99%